Pemberdayaan Masyarakat Melalui Penguatan Budaya Lokal dan Pelestarian Lingkungan Hidup - Putri Rahminda; Solfema Solfema; Lili Dasa Putri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Strengthening local culture and preserving the environment are important ways to build a sustainable society. Research shows that community-based approaches such as ProKlim and green villages can increase citizen awareness and participation in protecting the environment and culture. This study looks at local efforts to manage sustainable ecosystems and integrate cultural values when building sustainable tourist attractions. The success of this program depends on the active participation of the community in maintaining cleanliness, environmental conservation and preserving cultural heritage. It is hoped that this investigation will produce new findings that will help the development of an environmentally and culturally conscious community.